Helicobacter hepaticus Infection Promotes the Progression of Liver Preneoplasia in BALB/c Mice via the Activation and Accumulation of High-Mobility Group Box-1 - Cao, Shuyang; Miao, Jiancheng; Qian, Miao; Zhu, Chen; Ding, Shiping; Yin, Jun; Zhu, Liqi; Zhang, Quan (Frontiers in Microbiology, 2022)
It has been documented that Helicobacter hepaticus (H. hepaticus) infection is linked to chronic hepatitis and fibrosis in male BALB/c mice. However, the mechanism underlying the H. hepaticus-induced hepatocellular carcinoma is not fully known. In this study, male BALB/c mice were infected with H. hepaticus for 3, 6, 12 and 18 months. H. hepaticus colonization, histopathology, expression of proinflammatory cytokines, key signaling pathways and protein downstream high-mobility group box-1 in the liver were examined. Our data suggested that the H. hepaticus colonization level in the colon and liver progressively increased over the duration of the infection. H. hepaticus-induced hepatic inflammation and fibrosis were aggravated during the infection, and hepatic preneoplasia developed in the liver of infected mice at 12 and 18 MPI. H. hepaticus infection increased the levels of alanine aminotransferase and aspartate aminotransferase in the infected mice. Additionally, the mRNA levels of IL-6, TNF-α, TGF-β and HMGB1 were significantly elevated in the liver of H. hepaticus-infected mice from 3 MPI to 18 MPI as compared to the controls. In addition, Ki67 was increased throughout the duration of the infection. Furthermore, HMGB1 protein was activated and translocated from the nucleus to the cytoplasm in the hepatocytes, and activated the proteins of Stat3 and MAPK (Erk1/2 and p38) upon H. hepaticus infection. In conclusions, these data demonstrated that male BALB/c mice infected with H. hepaticus are prone to suffering hepatitis and developing into hepatic preneoplasia. Furthermore, we showed that H. hepaticus-induced liver preneoplasia is closely correlated with the activation and accumulation of HMGB1.